Content development for a new item-bank for measuring multifocal contact lens performance - Elsa Albero-Ros; Amalia Lorente-Velázquez; Mariano González-Pérez (SpringerOpen, 2024)
Abstract Background Presbyopia is an age-related condition that causes a decreased ability to focus on nearby objects. Multifocal contact lenses are commonly used to address this issue. However, there seems to be a notable dissatisfaction among multifocal contact lens wearers. The absence of a reliable instrument to measure the patient's perspective, despite the widespread use of this method, highlights the need for further research in this area. Objective The objective of this study is to develop an item-bank integrating all domains necessary to assess the patient's perspective on multifocal contact lens performance, offering a comprehensive measure. The item-bank will ensure a high level of content validity, be self-administered, and will initially be available in Spanish. The aim of this tool is to serve as a valuable resource for research and optometric clinics, facilitating the follow-up of patients with presbyopia who wear multifocal contact lenses or those who are newly starting to use them. Methodology The MCL-PRO item bank, followed a systematic and step-wise inductive approach to gather information, following the recommendations outlined in the COSMIN guidelines and similar studies. The process involved the following steps: (1) Literature review and relevant existing items identification (2) Social media review, (3) Semi-structured focus groups, (4) performing qualitative analysis, (5) refining and revising the items, and (6) generating the content of the item bank. Results A total of 575 items were included in the item-bank hosted under 8 different domains that were found to be important for presbyopic population: visual symptoms (213), activity limitation (111), ocular symptoms (135), convenience (36), emotional well-being (33), general symptoms (16), cognitive issues (21) and economic issues (10). Conclusion The item-bank created has followed standardised methodology for its development and encloses all the aspects for MCL performance evaluation from patients perspective.